A survey on the implementation of environmental health monitoring in mouse facilities in German-speaking countries - Esther Mahabir; Katja Schmidt; Thomas Kolbe; Stephanie Buchheister; Manuel Miller (PLoS ONE, 2025)
The health status of laboratory animals plays a decisive role not only for the health and welfare of the animals but also for the validity of study results. In recent years, there has been an increasing number of publications on environmental health monitoring (EHM), which uses molecular biological methods to detect nucleic acids of infectious agents in individually ventilated cage systems, e.g. in exhaust air dust. This monitoring strategy can reduce the number of mice used for health monitoring in conformity with the 3Rs. Numerous studies have shown that EHM is reliable and sensitive and is, therefore, a useful method for health monitoring of mice. An online survey was created to assess the prevalence of the use of EHM in Germany, Austria, and Switzerland and to better understand the factors influencing its use in animal facilities. The survey revealed that the majority of facilities primarily equipped with individually ventilated cage systems already use EHM to varying degrees, replacing between 8 and 1200 animals per year and facility. However, the predominant strategy is still the use of (sentinel) animals for health monitoring. Beliefs on factors such as cost, reliability and the number of false-positive results differ significantly between facilities that predominantly use either animals or EHM. Additionally, the choice of monitoring strategy may be influenced by the existing cage system and the availability of a decontamination option for the equipment. The evaluation of the survey showed that there is still a gap in knowledge and a demand for specific training on the topic of health monitoring and especially on EHM.